The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.4049/jimmunol.172.10.5838
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TREM-Like Transcript-1, a Platelet Immunoreceptor Tyrosine-Based Inhibition Motif Encoding Costimulatory Immunoreceptor that Enhances, Rather than Inhibits, Calcium Signaling via SHP-2

Abstract: To date, immunoreceptor tyrosine-based inhibition motifs (ITIMs) have been shown to mediate inhibitory properties. We report a novel triggering receptor expressed on myeloid cells (TREM) family member, TREM-like transcript-1 (TLT1), which differs from the activating members because its cytoplasmic tail contains two ITIMs at Y245 and Y281. A TLT1 splice variant (TLT1sp) encodes a different cytoplasmic tail lacking ITIMs. Both isoforms are expressed in resting platelet α-granules, which are up-regulated to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 16 publications
3
91
0
Order By: Relevance
“…The latter action is similar to that of G6b-B, which upon crosslinking by a specific antibody inhibits activation of platelets by the GPVI-specific agonist, collagen-related peptide, and the G protein-coupled receptor agonist ADP (13). In contrast, the ITIM receptor, TREM-1, which is present on platelet intracellular granules, is translocated to the surface of activated platelets and reinforces platelet activation (16).…”
mentioning
confidence: 83%
“…The latter action is similar to that of G6b-B, which upon crosslinking by a specific antibody inhibits activation of platelets by the GPVI-specific agonist, collagen-related peptide, and the G protein-coupled receptor agonist ADP (13). In contrast, the ITIM receptor, TREM-1, which is present on platelet intracellular granules, is translocated to the surface of activated platelets and reinforces platelet activation (16).…”
mentioning
confidence: 83%
“…The potential biological significance of the sTLT-1 fragment is reinforced by the existence of 2 splice variants with limited or absent intracellular domains. The first is the most abundant TLT-1 mRNA species and possesses an extracellular domain identical to that of full-length TLT-1 but only a 16-aa cytoplasmic domain (18). The second form was recently identified in our laboratory and encodes only the TLT-1 extracellular domain (A.V.…”
Section: Discussionmentioning
confidence: 99%
“…Other receptors encoded within the TREM gene cluster such as TLT1 lack the conserved transmembrane lysine residue, but contain within their own cytoplasmic domain tyrosinebased signaling motifs (11). In the case of TLT1, there is an ITIM, which mediates recruitment of SHP1 and SHP2 (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…TLT1 is stored in the ␣-granules of platelets and is quickly redistributed to their surface upon activation. It has also been reported that ligation of this receptor promotes rather than inhibits Ca 2ϩ mobilization through an interaction with SHP2, although the physiological relevance of this, as well as the natural ligand responsible, have yet to be determined (12).…”
Section: Trem-like Transcript 2 Is Expressed On Cells Of the Myeloid/mentioning
confidence: 99%